Antibacterial activity of the biogenic volatile organic compounds from three species of bamboo - Duan, Yifan; Lv, Bingyang; Zhang, Chunlong; Shi, Lisha; Li, Jingting; Liu, Yanjun; Chen, Qibing (Frontiers in Plant Science, 2024)
Plant biogenic volatile organic compounds (BVOCs) possess ecological functions in bacteriostasis and air purification. To analyze the antimicrobial activities of BVOCs of different bamboo species and growth status, pure bamboo forests comprising three common bamboo species-Phyllostachys edulis, Bambusa emeiensis, and Phyllostachys violascens-were selected as the research objects to determine the inhibitory capacity of bamboo forests in different sampling sites as well as the inhibitory capacity of bamboo in ex vivo condition leaves against 6 airborne common microorganisms. The microbe counts in grassland in the same area was measured as control treatment. The results showed that except for the P. violascens in Ya'an, the airborne microbial content of the sampling sites in bamboo forests was significantly lower relative to that of grassland in the same area, and inhabition rate reached 74.14% in the P. violascens forest in Dujiangyan. P. edulis forest at Ya'an and P. violascens forest at Ya'an had significantly lower inhibition rates than the other sampling sites, and there was no significant difference in the inhibition rates of the rest of the bamboo forest.The bacterial inhibition rate of bamboo leaves in ex vivo conditions varied with bamboo species and bacterial strains, with higher antibacterial activity against Gram-negative bacteria overall. Escherichia coli was sensitive to B. emeiensis leaves, while Staphylococcus aureus and Bacillus subtilis were sensitive to P. violascens leaves. Moreover, Candida albicans, S. cremoris, and Shigella Castellani were sensitive to P. edulis leaves. An analysis of the BVOCs composition from P. edulis collected in Changning by SPME-GC/MS revealed that the relative content of ocimene was obviously higher than other components. This study showed that P. edulis BVOCs have strong inhibitory ability to the tested microorganisms, and its main constituent Ocimene has health benefit. P. edulis has the potential to become a forest recreation bamboo species.